Sử dụng phương pháp WebQuest trong tổ chức dạy học tích hợp giáo dục vì sự phát triển bền vững chủ đề “Hệ sinh thái và vấn đề phát triển bền vững” (Sinh học 12) - Hà, Văn Dũng (Tạp chí Giáo dục, 2024)
The global trend of integrating Education for Sustainable Development (ESD) into school curricula is being promoted by UNESCO. In Vietnam, to achieve the goal of ESD, all subjects in general education need to incorporate this content to an appropriate extent. When the conditions for organizing teaching are limited and the topics require activities in real-world settings, the WebQuest method is appropriate for both teachers and students nowadays. Using theoretical research methods, this paper analyzes several conceptual tools, thereby proposing a process for organizing integrated ESD teaching on the topic “Ecosystems and Sustainable Development” (Biology 12), along with an illustrative example through a local ecosystem-related topic, “The Ba Vi National Park Ecosystem and Sustainable Development” using the WebQuest method. This study not only brings direct benefits to teachers and students in organizing teaching activities but also has broader significance in building an education system oriented towards sustainable development.